Penambahan Tenebrio molitor Pada Pakan Terhadap Karakteristik Hedonik dan Mutu Hedonik Daging Ayam Mentah dan Matang - Wahyuni Wahyuni; Niken Ulupi; Nahrowi Nahrowi (Wahana Peternakan, 2022)
ABSTRACT Tenebrio molitor is an insect larvae that has the potential as a protein source for poultry feed. However, no exploratory research has been found on the quality of poultry meat reared with feed containing these insect larvae. The purpose of this study was to evaluate the hedonic and hedonic quality characteristics of fresh and boiled chicken meat in terms of color, texture, aroma and taste of broiler chicken fed with Tenebrio molitor meal. This research method is experimental using a completely randomized design (CRD). As a treatment, there were two types of feed, namely feed containing 5% MBM as control (R0) and feed containing 5% Tenebrio molitor meal (R1). The treatment was repeated five times, ten chickens for each replication. The results of hedonic and hedonic quality observations were analyzed descriptively. Based on hedonic quality characteristics; the color of the raw meat is redder, the aroma is less fishy, and the taste of cooked meat is more savory. And, in hedonic; broiler chicken that is fed a feed containing Tenebrio molitor meal is preferred by the panelists. So it can be concluded that broiler chicken meat that is fed with Tenebrio molitor meal is better than chicken meat that consumes MBM. Key Words: Chicken meat, Hedonic,Tenebrio molitor